2018
DOI: 10.1152/ajpgi.00346.2017
|View full text |Cite
|
Sign up to set email alerts
|

The impact of short-chain fatty acids on GLP-1 and PYY secretion from the isolated perfused rat colon

Abstract: The colonic epithelium harbors a large number of endocrine cells, but little is known about the endocrine functions of the colon. However, the high density of glucagon like peptide-1 (GLP-1)- and peptide-YY (PYY)-secreting L cells is of great interest because of the potential antidiabetic and antiobesity effects of GLP-1 and PYY. Short-chain fatty acids (SCFAs) produced by local bacterial fermentation are suggested to activate the colonic free fatty acid receptors FFAR2 (GPR43) and FFAR3 (GPR41), stimulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
197
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(228 citation statements)
references
References 69 publications
3
197
0
6
Order By: Relevance
“…SCFAs can activate the GLP‐1 signaling pathway (35). Furthermore, we found that compound A6 increased SCFA of mouse feces.…”
Section: Resultsmentioning
confidence: 99%
“…SCFAs can activate the GLP‐1 signaling pathway (35). Furthermore, we found that compound A6 increased SCFA of mouse feces.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with previously reported effect of butyrate or SCFAs on the intestinal function, obesity, and NAFLD. SCFAs have also been reported to show antiobesity effect in animal models, through affecting the secretion of glucagon‐like peptide‐1 and peptide tyrosine tyrosine in the intestine (Christiansen et al, ). I has also been reported that the probiotic mixture of Lactobacillus and Bifidobacterium alleviates inflammation in NAFLD rats through the action of metabolite butyrate (Liang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Through luminal and especially vascular infusion of acetate, propionate and butyrate, they observed that acetate and butyrate increased colonic glucagon-like peptide-1 (GLP-1) secretion with increased intracellular cAMP concentrations but independent in FFAR2/FFAR3 activation. The results suggested that all blood circulation, nerve and paracrine might play a part in the SCFAs-stimulated GLP-1 secretion [34]. Another research demonstrated that SCFAs decreased food take by activating vagal afferent via intraperitoneal injection of three SCFA molecules (acetate, propionate and butyrate) in fasted mice and switching off the vagal afferents of hepatic branch and capsaicin-sensitive sensory nerves [35].…”
Section: Scfasmentioning
confidence: 95%